Yucky poo - Caraher, Kim (Macmillan Education Australia South Yarra, 1998)
Yucky Poo is a children's book by Vivian French, illustrated by Sue Heap. The story is a fun and lighthearted exploration of bodily functions, specifically focusing on the topic of poo. It humorously explains the natural process of digestion, from the food we eat to how it turns into waste, and emphasizes that "everyone does it." The book uses playful language and colorful illustrations to help children understand a sometimes embarrassing topic in an engaging and educational way, promoting comfort and curiosity about the human body.